Municipal flood risk sharing in Canada: A policy instrument analysis. Issue 4 (2nd October 2017) - Thistlethwaite, Jason; Henstra, Daniel
Abstract : Although municipal governments have long dealt with flood hazards, escalating damage to property and infrastructure has prompted greater interest in policies that share the responsibility for risk reduction and the burden of costs with other levels of government and non-governmental actors. However, flood risk sharing is a significant policy challenge, because it requires consideration of the consequences of flooding, in addition to its probability, and it involves engagement with a broader pool of stakeholders in managing flood risk. Scholarly literature on risk sharing tools available to Canadian municipalities and the extent of their adoption is scarce. To address this gap, this paper identifies a set of policy tools by which municipalities can share flood risk, and assesses how and the extent to which they are adopted in the cities of Calgary, Alberta, and Toronto, Ontario. This analysis reveals that, despite a diverse range of policy options, risk sharing tools are underutilized and continue to be informed by single hazard-based design standards rather than an assessment of flood risk.